Global Value Chains and External Adjustment : Do Exchange Rates Still Matter? - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2019)
The paper explores how international integration through global value chains shapes the working of exchange rates to induce external adjustment both in the short and medium run. The analysis indicates that greater integration into international value chains reduces the exchange rate elasticity of gross trade volumes. This result holds both in the short and medium term, pointing to the rigidity of value chains. At the same time, greater value chain integration is associated with larger gross trade flows, relative to GDP, which tends to amplify the effect of exchange rate movements. Overall, combining these two results suggests that, for most countries, integration into global value chains does not materially alter the working of exchange rates and the benefits of exchange rate flexibility in facilitating external adjustment remain.